Malignant Cervical Lymphadenopathy among Fine Needle Aspiration Cytology in a Tertiary Care Center in Far Western Nepal: A Descriptive Cross-sectional Study - Shreepaili, Ashok; Dhakal, Sushil (Med Phoenix, 2022)
Introduction Metastatic cervical lymphadenopathy is a diagnostic and therapeutic challenge. The utility of Fine Needle Aspiration Cytology is well established in the diagnosis of metastatic lymph nodes, new-onset, or recurrence. This study aims to find the prevalence of metastatic cervical lymphadenopathy among fine needle aspiration cytology in a tertiary care center in far western Nepal. Materials and Methods This is a descriptive cross-sectional study carried out in Seti Provincial Hospital and Maya Metro Hospital, Dhangadhi, Kailali, Nepal between July 2018 to December 2019. Total 534 cervical lymph node aspirations were performed during this period out of which 48 cases were cytologically proven as malignant lymph nodes. Clinical charts and cytology reports of patients with malignant lymph nodes were reviewed. Results Out of 534 cervical lymph node aspirations performed during the study period, the number of malignant lymph nodes was 48 (8.99%). Among malignant lymph nodes (n=48), primary hematolymphoid malignancy was 14 (29.17%) and metastatic cervical lymphadenopathy was 34 (70.83%). Metastatic squamous cell carcinoma was the most common etiology of metastatic cervical lymphadenopathy followed by nasopharyngeal carcinoma and papillary carcinoma of the thyroid. Conclusion Fine needle aspiration cytology has been proved to be a valuable tool in the initial evaluation of metastatic cervical lymphadenopathy in resource-limited settings. Metastatic squamous cell carcinoma is the most common diagnosis in metastatic cervical lymphadenopathy.